1988
DOI: 10.1007/bf01536989
|View full text |Cite
|
Sign up to set email alerts
|

Oral feeding of isolated lectins from red kidney bean stimulates rat small intestinal mucosal DNA synthesis and crypt cell division

Abstract: A lectin preparation containing enterokinase inhibitor purified or partially purified from red kidney bean (RKB) when fed to weanling rats was shown to cause small intestinal hyperplasia. To see if this hyperplastic effect on the rat small intestine was due to the mitogenic properties of the isolated lectin, male weanling rats were fed a chow containing 0.1% of the isolated lectin for six days. Age-matched control rats were fed regular chow. Both control and lectin-fed rats were sacrificed at one, two, three, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
7
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 24 publications
3
7
0
Order By: Relevance
“…This was found even after 23 days of feeding, a duration expected to allow full adaptation. In the work of Tajiri et al (23), the distal small intestines showed no increase in DNA content whereas we found a trophic effect in all areas of the small bowel. These workers suggest that red kidney bean lectin may become inactivated during passage down the intestines so that there is insufficient material remaining to interact with the distal region.…”
Section: Methodssupporting
confidence: 45%
See 4 more Smart Citations
“…This was found even after 23 days of feeding, a duration expected to allow full adaptation. In the work of Tajiri et al (23), the distal small intestines showed no increase in DNA content whereas we found a trophic effect in all areas of the small bowel. These workers suggest that red kidney bean lectin may become inactivated during passage down the intestines so that there is insufficient material remaining to interact with the distal region.…”
Section: Methodssupporting
confidence: 45%
“…One might predict that enzyme activities would rise in support of the observed increases in mucosal weight, protein, and DNA. However, hyperplasia can occur in the crypt region rather than the villus, as was previously reported to result from feeding red kidney bean lectin (23). Inasmuch as brush border enzymes are immature on the crypt cells, no increase in microvillus enzyme activity would occur.…”
Section: Methodsmentioning
confidence: 81%
See 3 more Smart Citations